A conceptual model for production and evaluation of Sahiwal bulls in associated herd system using embryo transfer - GANDHI, R S; SINGH, AVTAR (The Indian Journal of Animal Sciences, 2013)
A conceptual model for production and evaluation of Sahiwal bulls through MOET has been proposed for bringing about faster genetic improvement in milk yield. A total of 9 349 lactational milk yield records of 2 374 Sahiwal cows from 5 farms were used to generate parameters for this study. Assuming a herd size of 500 breedable females: 16 transferable embryos/year (4 embryos/flush. 4 flushings/year); and joint effect of conception rate. survivability up to maturity and culling on poor growth rate to be 0.25, the expected genetic gains from juvenile and adult MOET schemes were estimated to be 2.303 and 2.950% of herd mean (1788 kg). It was concluded that wherever infrastructure for cryopreservation and transfer of embryos is available, MOET should be used for enhancing genetic improvement in milk yield ofSahiwal cattle.